Implications of Anti derivatives in the Practical Life of Students’ Future Career - Adhikari, Deepak; Koirala, Siddhi Prasad (Journal of Advanced Academic Research, 2024)
This study looks into the practical applications of anti derivatives in the academic and professional life of engineering students. The study's goal is to relate theoretical knowledge gained throughout academic studies to its application in real-world circumstances. The study explores how students use anti derivatives in practical circumstances, analyzes problems encountered in their professional application, and measures students' recall of important ideas and theories. Semi-structured interviews were conducted with 58 engineering students from various domains to find significant differences in gender across disciplines. While the majority of participants were men, certain fields, such as chemical engineering, saw increasing female involvement. The findings highlight the various applications of anti derivatives. Civil engineers frequently use them for area calculations, structural analysis, and project assessments, whereas mechanical engineers use them for volumetric calculations, control systems, and energy studies. Electronic engineers claimed applications in signal processing, fluid dynamics, and thermal analysis. Chemical engineers use anti derivatives in reactor design, thermodynamics, and plant construction, whereas information technology professionals use them in data science and network theory. Despite their importance, difficulties such as limited practice and comprehension were identified, limiting practical application. The study also highlights the respondents' varying levels of satisfaction, with training methods having an important effect on their assessment of anti derivatives' applicability. Recalling concepts frequently relied on resources such as books, internet tools, and advice from peers and teachers.